الملكة ستراتونيكي وزواجها السياسي: وسيلة لتعزيز السلطة والتحالفات في العصر الهلنستي (Comprehensive Journal of Science, 2026)
This research summarizes the role of Queen Stratonice (Stratones II) in the Hellenistic era, highlighting her royal status and political influence within the Seleucid dynasty , The first section examines her family origins and her connection to power, while the second focuses on her political marriage as a tool for strengthening alliances and reshaping the balance of power, It concludes that she was an active player on the political scene, not merely a pawn in power struggles.
Keywords: Stratonice, political marriage,Hellenistic period, female power